A randomised phase II clinical trial of nab-paclitaxel and carboplatin compared with gemcitabine and carboplatin as first-line therapy in advanced squamous cell lung carcinoma (C-TONG1002). (March 2019) - Wang, Zhen; Huang, Cheng; Yang, Jin-Ji; Song, Yong; Cheng, Ying; Chen, Gong-Yan; Yan, Hong-Hong; Ben, Xiao-Song; Wang, Bin-Chao; Xu, Chong-Rui; Jiang, Ben-Yuan; Zhou, Qing; et al.
Abstract: Background: N ab -paclitaxel/carboplatin ( nab -PC) and gemcitabine/carboplatin (GC) are the standard first-line chemotherapy in non–small cell lung carcinoma. Up to now, there is no head to head trial to compare nab -PC with GC in advanced squamous cell lung carcinoma. Patients and methods: A multicentre randomised phase II trial was performed to compare the efficacy and safety for nab -PC with GC in previously untreated patients with advanced squamous cell lung carcinoma. The primary end-point was objective response rate (ORR). Progression-free survival (PFS), overall survival (OS), treatment-related adverse events and quality of life (QoL) were also analysed. Results: Totally 127 participants were eligible for this study (62/65 nab -PC/GC). N ab -PC has higher ORR than GC without statistical significance (42% versus 27%, P  > 0.05). After a median follow-up of 14.5 months, both PFS and OS had no difference between the two arms (6.7 versus 5.8 months, hazard ratio [HR] 0.75, P  = 0.143; 11.6 versus 14.4 months, HR 0.92, P  = 0.846). Both regimens were well tolerated; however, more dose reduction occurred after cycle 2 in GC (27%) than in nab -PC (12%) ( P  < 0.05). Significant QoL improvement measured by trial outcome index was seen in nab -PC than in GC ( P  < 0.05). Conclusions: The first-line nab -PC and GC had the same response, PFS, and OS in patients with advanced squamous cell lung carcinoma. N ab -PCM has advantage over GC in QoL improvement. Trial registration number: NCT01236716. Highlights: N ab -paclitaxel/carboplatin and gemcitabine/carboplatin had the same efficacy in advanced squamous cell lung carcinoma. Both progression-free survival and overall survival had no difference between the two arms. Both nab -PC and GC are well tolerated. N ab -PC had advantage of improving quality of life.